Predicting the inflation rate in Malaysia using sukuk term structure - Humaida Banu Samsudin; Nur Atikah Mohamed Rozali; Dini Naziha Mohamad (Pusat Pengajian Sains Matematik, Fakulti Sains dan Teknologi, Universiti Kebangsaan Malaysia, 2016)
The ability to forecast inflation rate accurately is vital since inflation has a big impact on both society and the country in general. One of the methods used to predict inflation rate is by observing the term structure. There have been many studies done on term structure of conventional bonds but hardly any on sukuk. Therefore, this study aims to test the viability of the term structure of sukuk on predicting the inflation rate in Malaysia, with and without taking into factor term premiums, and compare the predictions with those of the conventional bonds. The results are also compared to a benchmark autoregressive (AR) model of the inflation rate. The monthly interest rate data starting from October 2006 to March 2014 for Malaysian Government Securities (MGS), which is a conventional bond and Government Investment Issues (GII), which is an Islamic bond, were used in this study. Consumer Price Index data from the year 2005 until 2014 were also collected to calculate inflation rates. The one-month interest rate was used to observe the existence of term premium. An autoregressive distributed lag (ARDL) model was chosen to forecast six-month-ahead inflation rates using MGS and GII data with and without accounting for term premiums. The first part of the analysis revealed that term premiums are nonzero and not constant. Furthermore, forecasting results showed that without considering term premiums, neither MGS nor GII term structure was able to accurately predict the six-month-ahead inflation rate. However, incorporating term premiums into the term structure would result in a better forecast of the inflation rate compared to the benchmark AR model. As such, it is hoped that this will spur more interest in the development of sukuk and Islamic economics in terms of research.